Arabic literary culture in Southeast Asia in the seventeenth and eighteenth centuries - Peacock, Andrew Charles Spencer, 1976- (Leiden ; Boston)
xix, 514 sayfa
Keywords: “This groundbreaking work studies the Arabic literary culture of early modern Southeast Asia on the basis of largely unstudied and unknown manuscripts. It offers new perspectives on intellectual interactions between the Middle East and Southeast Asia, the development of Islam and especially Sufism in the region, the relationship between the Arabic and Malay literary traditions, and the manuscript culture of the Indian Ocean world. It brings to light a large number of hitherto unknown texts produced at or for the courts of Southeast Asia, and examines the role of royal patronage in supporting Arabic literary production in Southeast Asia.“ --